(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
Current examination of the student’s readiness for professional mobility should be carried out based on the following set of methods: test; questionnaire; analysis of the results of self-study work and practical assignments, conducting control work.